2014
DOI: 10.1186/1476-511x-13-172
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomic analysis of retinoic-acid induced dyslipidemia in congenic rat model

Abstract: BackgroundAll-trans retinoic acid (ATRA, tretinoin) is a vitamin A derivative commonly used in the treatment of diverse conditions ranging from cancer to acne. In a fraction of predisposed individuals, the administration of ATRA is accompanied by variety of adverse metabolic effects, particularly by the induction of hyperlipidemia. We have previously derived a minimal congenic SHR.PD-(D8Rat42-D8Arb23)/Cub (SHR-Lx) strain sensitive to ATRA-induced increase of triacylglycerols and cholesterol under condition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…SIRT3 deacetylates and activates OPA1 to regulate mitochondrial dynamics to protect cells from doxorubicin‐mediated cell death (Samant et al ., ). SIRT3 is likely to affect a specific response to ATRA (Krupkova et al ., ). This possibility is interesting and warrants further investigation regarding ATRA‐regulated OPA1 deacetylation in our work.…”
Section: Discussionmentioning
confidence: 97%
“…SIRT3 deacetylates and activates OPA1 to regulate mitochondrial dynamics to protect cells from doxorubicin‐mediated cell death (Samant et al ., ). SIRT3 is likely to affect a specific response to ATRA (Krupkova et al ., ). This possibility is interesting and warrants further investigation regarding ATRA‐regulated OPA1 deacetylation in our work.…”
Section: Discussionmentioning
confidence: 97%
“…For transcriptomic data, after evaluation of hybridization, quality control, and the data normalization by robust multi-array analysis, gene expression was compared between the SHR and the SHR-Dca strains using PARTEK Genomics Suite 6.6 (Partek, Inc., Chesterfield, MO, USA). Transcripts found to be significantly differentially expressed by more than 1.2-fold between the two strains after multiple comparison adjustment using the false discovery rate method (FDR<0.05) were included in gene enrichment and pathway analyses, which were performed using Ingenuity Pathway Analysis software (application build 364062M, content version 26127183) as described previously (Krupkova et al 2014, Sedova et al 2012.…”
Section: Statistical and Pathway Analysesmentioning
confidence: 99%
“…In addition to its role in adipogenesis, control of hepatic gluconeogenesis ( Chen et al, 2014 ), and cardiac hypertrophy ( Liska et al, 2017 ), genetic variation in human ZBTB16 was associated with increased obesity parameters and higher total and LDL cholesterol ( Bendlova et al, 2017 ). We have previously shown that rats carrying specific Zbtb16 allele are particularly sensitive to HSD, glucocorticoids, and retinoic acid in terms of induction of metabolic dysfunction ( Krupkova et al, 2014 , 2018 ). Therefore, we hypothesized that maternal HSD intake during pregnancy and lactation would program the offspring to develop metabolic alterations in adulthood and that these effects may be, to a certain extent, modified by genetic variation in Zbtb16 .…”
Section: Introductionmentioning
confidence: 99%